Retrospective cohort study of long-acting injectable (LAI) antipsychotic initiation in the inpatient setting: impact of LAI characteristics on transition and continuation of care among patients with schizophrenia in the USA - Rashmi Patel; Christian Liman; Mayowa Oyesanya; Sheryl Ker; Aishwarya Jayaraman; Kelli R Franzenburg; Rolf T Hansen; Mike J Philbin; Stephen Thompson (BMJ Open)
Objectives To investigate long-acting injectable (LAI) antipsychotic prescribing patterns and their associations with transition and continuation of care and healthcare resource utilisation (HCRU) for patients with schizophrenia in the USA.Design A retrospective cohort study.Setting Electronic health record data from adults in the USA with schizophrenia were extracted from the NeuroBlu Database V.21R2.Participants Adults (aged ≥18 years) with a schizophrenia diagnosis who initiated LAI antipsychotic treatment during psychiatric inpatient admission. The index date was the date of LAI initiation. Patients who had ≥1 primary, secondary or tertiary ICD-9/10 (International Classification of Diseases) diagnosis of schizophrenia at clinical sites that had both inpatient and outpatient facilities were included.Primary outcome measures Transition-of-care (eg, risk of rehospitalisation, number of hospital readmissions, number of outpatient visits post discharge), continuation-of-care (eg, first treatment path after discharge, time to index LAI discontinuation and number of patients who restarted LAIs after discontinuation) and HCRU endpoints (eg, length of stay of index hospitalisation and estimated cost for psychiatric outpatient visits pre-index and post-index) were the primary outcome measures.Results A total of 1197 patients were included who initiated an LAI in an inpatient setting. Of 339 patients with ≥3 months pre-index and post-index data, median time to rehospitalisation was 135 days. Patients discharged taking an LAI alone had lower frequency of rehospitalisation (incidence rate ratio (IRR)=0.62 (95% CI, 0.46 to 0.84)), lower risk of longer hospital stays (IRR=0.60 (95% CI, 0.43 to 0.84)), lower risk of becoming rehospitalised (HR=0.49 (95% CI, 0.35 to 0.69)) and lower risk of outpatient visits (IRR=0.50 (95% CI, 0.36 to 0.70)) versus patients co-prescribed an oral antipsychotic (LAI+OA). Patients discharged taking an LAI dosed once every 1–2 months or once every 2 weeks had lower frequency of rehospitalisation (IRR=0.85 (95% CI, 0.64 to 1.14)), lower risk of longer hospital stays (IRR=0.90 (95% CI, 0.70 to 1.15)) and lower risk of becoming rehospitalised versus an LAI dosed once every 2 weeks; risk of becoming rehospitalised was no different (HR=1.00 (95% CI, 0.76 to 1.32)) and risk of outpatient visits was greater (IRR=1.25 (95% CI, 0.96 to 1.63)). During hospitalisation, 73.4% of patients were co-prescribed an OA, most frequently risperidone, with their index LAI. From pre-admission to post-discharge, psychiatric clinic costs significantly increased (US$14 231, p<0.01 post-discharge vs pre-admission) among patients co-prescribed an OA. For patients who were prescribed an LAI alone there was minimal change in costs from pre-admission to post-discharge (p=0.068). At 12 months post-index, 75.3% of patients discontinued LAIs, dosed once every 1–2 months versus LAIs, dosed once every 2 weeks (86.5%) and median days to discontinuation was longer (67 (IQR 60–91) vs 32 (IQR 28–49).Conclusions Patients prescribed a combination of LAI and OA at discharge had a higher risk of rehospitalisation compared with those prescribed LAI alone. Additionally, the study findings suggest that patients are more likely to be prescribed oral risperidone, the most frequently used second-generation OA, which may support an easier transition to an LAI of the same molecule.